Estimating Gross Regional Domestic Product (GRDP) District/City in East Nusa Tenggara with Spatial Dynamic Panel Data - Febrya Christin Handayani Buan; Rahma Fitriani; Nurjannah Nurjannah (Sekolah Pascasarjana Universitas Brawijaya, 2021)
East Nusa Tenggara Province has the lowest Gross Regional Domestic Product (GRDP) value in Indonesia. The local governments try to increase the value of GRDP by providing capital for productive businesses, increasing human resources, and managing the economic sector in each district/city. The GRDP value is influenced by dynamic economic factors. In a functional region, GRDP values in a region are correlated with neighboring regions. Regions that have homogeneous characteristics will tend to have the same economic condition, therefore indicating there is spatial dependence. Therefore, to know the pattern of GRDP value should be doing periode observed use panel data. Model panel data that can accommodate the effect of each factor on GRDP value has dynamic and dependence spatial, the model can be more useful to capture them. This study will apply the model to the cast of GRDP value in the district/city of East Nusa Tenggara Province with economic factors affecting GRDP value is labor (L), population (P), investment (Inv), and locally generated revenue (LGR). The results of variable estimated the found that significantly affect the GRDP values are investment (Inv) and locally generated revenue (LGR), furthermore GRDP value affect by GRDP value in the previous period and GRDP value by neighbor regions.